More predicament than spectacle conducting subnational political research in the Philippines - Walsh, Thomas P. (1977)
Fulfillment of all the basic pre-field work requirements in undertaking crossnational field research (preparation of research instruments, establishing liaison with governmental agencies, administration of pre-tests of questionnaires, etc., does not exempt a political scientist from encountering unanticipated problems in the course of his research. Such predicamental situations emerged during an eight-month field study of Philippine provincial governors - and are related here with the insights and lessons learned. Future researchers on local Filipino political elites are therefore encouraged not only to concern themselves with pre-fieldwork preparations but also to be ready to respond effectively to actual field research
predicaments.
Keywords: Public administration -- Research